2016
DOI: 10.1108/ijrdm-08-2015-0133
|View full text |Cite
|
Sign up to set email alerts
|

Shopping for kids’ luxury brands: young mothers’ identity quest in retail spaces

Abstract: Purpose The purpose of this paper is to focus on mothers as key influencers in luxury retailing contexts. Design/methodology/approach Using a semiotic interpretation of mothers’ discourses, the authors underline the identity motivations for purchasing luxury apparel for their pre-adolescent children. Findings The paper shows that when shopping for luxury brands for their pre-adolescent children, mothers manage discrepancies between their “real” and “idealised” selves as well as the pushes and pulls of bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Instead, by looking at the new products that have been recently launched by Bonia and the way the company is marketing the products, it seems that the company is targeting the younger generation instead of adults who work as high-ranking officers in the corporate sector. In fact, the findings have proven that the young generation is conscious of luxury brands (Giovannini et al, 2015), because nowadays, more mothers are prone to purchase a luxury brand product for their children (Silhouette-Dercourt and De Lassus, 2016). Further findings also indicate that young ladies tend to be more impulsive concerning prestige and choosing a well-known branded product is a higher priority than being price conscious (Muratore and Muratore, 2016).…”
Section: Analysis and Discussionmentioning
confidence: 97%
“…Instead, by looking at the new products that have been recently launched by Bonia and the way the company is marketing the products, it seems that the company is targeting the younger generation instead of adults who work as high-ranking officers in the corporate sector. In fact, the findings have proven that the young generation is conscious of luxury brands (Giovannini et al, 2015), because nowadays, more mothers are prone to purchase a luxury brand product for their children (Silhouette-Dercourt and De Lassus, 2016). Further findings also indicate that young ladies tend to be more impulsive concerning prestige and choosing a well-known branded product is a higher priority than being price conscious (Muratore and Muratore, 2016).…”
Section: Analysis and Discussionmentioning
confidence: 97%
“…Furthermore, young people learn to be future luxury consumers by virtue of their interactions with adults, especially their parents, which may generate conflicts that affect the well-being of the groups. For instance, many parents are facing situations in which their children are under the influence of social media and peer pressure to demand luxury brands, particularly luxury fashion brands (Silhouette-Dercourt and De Lassus 2016). This situation can leave parents who cannot afford the premium prices of luxury items feeling guilty (Batat and Tanner 2019).…”
Section: Conceptualizing Tlr: a Framework Linking Luxury With Well-be...mentioning
confidence: 99%
“…In addition to a mother's attempt to shape the child's identity through consumer socialization in the marketplace, children also make a mother; since consumption on behalf of children help women to construct their motherhood identity (Banister and Hogg, 2006). While Thomsen and Sorensen (2006) supported the idea that transition to motherhood identity is experienced by using the symbolic and material resources provided by the marketplace, studies revealed that, to impress others in their social network, mothers can construct their relational identity through purchasing premium items for their children, even when children cannot notice and appreciate it (Silhouette-Uluslararası İktisadi ve İdari İncelemeler Dergisi Dercourt and Lassus, 2016;Ozhan Dedeoglu, 2010). Therefore, mothers, as a market agent who make consumer decisions both on behalf of themselves and their children, are worthy for an analysis due to their potential for providing theoretical explanations for the research question whether consumer spending self-control of the same person changes depending on different modes of relation to oneself and others -i.e.…”
Section: Introductionmentioning
confidence: 99%